The Mitigation of Wildlife - Communities Conflict In Gunung Leuser National Park (Case Study of Timbang Lawan and Timbang Jaya Village, Bahorok Sub-District, Langkat Regency) - Wilda Hasanah Harahap; Pindi Patana; Yunus Afifuddin (Program studi Kehutanan USU, 2013)
Research on